2021
DOI: 10.1103/physrevb.103.096301
|View full text |Cite
|
Sign up to set email alerts
|

Comment on “Collective modes and gapped momentum states in liquid Ga: Experiment, theory, and simulation”

Abstract: We show, that the theoretical expression for the dispersion of collective excitations reported in [Phys. Rev. B 103, 099901 (2021)], at variance with what was claimed in the paper, does not account for the energy fluctuations and does not tend in the long-wavelegth limit to the correct hydrodynamic dispersion law.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…On the contrary, the Frenkel time seems to attain to the dynamics of the single liquid molecule which is definitely not the character in discussion here since hydrodynamics refers only to the long-wavelength collective dynamics. These points have been already discussed in the literature [92][93][94]. Recently Ref.…”
Section: A Theoretical Backgroundmentioning
confidence: 64%
“…On the contrary, the Frenkel time seems to attain to the dynamics of the single liquid molecule which is definitely not the character in discussion here since hydrodynamics refers only to the long-wavelength collective dynamics. These points have been already discussed in the literature [92][93][94]. Recently Ref.…”
Section: A Theoretical Backgroundmentioning
confidence: 64%
“…which is fundamental for all liquids [5][6][7][8]. Recently some of us [10] have demonstrated that one obtains results, which contradict the known dynamic properties of liquids, if the continuity equation is not taken into account. As a consequence of the absence of the continuity equation (5) in their treatment, BLZ claim that their longitudinal sound would come "from the mixing of energy fluctuations and longitudinal momentum fluctuations" (quoting BLZ [1]), at variance with textbook knowledge [5][6][7][8].…”
mentioning
confidence: 99%